Physiological Function of Rac Prophage During Biofilm Formation and Regulation of Rac Excision in Escherichia coli K-12 - Liu, Xiaoxiao (Sci Rep, 2015)
Rac or rac-like prophage harbors many genes with important physiological functions, while it remains excision-proficient in several bacterial strains including Escherichia coli, Salmonella spp. and Shigella spp. Here, we found that rac excision is induced during biofilm formation, and the isogenic stain without rac is more motile and forms more biofilms in nutrient-rich medium at early stages in E. coli K-12. Additionally, the presence of rac genes increases cell lysis during biofilm development. In most E. coli strains, rac is integrated into the ttcA gene which encodes a tRNA-thioltransferase. Rac excision in E. coli K-12 leads to a functional change of TtcA, which results in reduced fitness in the presence of carbenicillin. Additionally, we demonstrate that YdaQ (renamed as XisR) is the excisionase of rac in E. coli K-12, and that rac excision is induced by the stationary sigma factor RpoS through inducing xisR expression. Taken together, our results reveal that upon rac integration, not only are new genes introduced into the host, but also there is a functional change in a host enzyme. Hence, rac excision is tightly regulated by host factors to control its stability in the host genome under different stress conditions.